Impact response of different materials for sports mouthguards - Maria Moreira; João Carlos Ramos; Ana Messias; Maria Augusta Neto; Ana Paula Amaro; Paulo NB Reis (Fracture and Structural Integrity, 2021)
Up to this moment, there is no guideline regarding the materials to produce mouthguards. The most used is Ethylene-Vinyl Acetate (EVA). Studies indicate that laminating EVA sheets with rigid components could increase the protection capacities of the mouthguards whereas other studies suggest that only replacement of the material within it structure can increase energy absorption. The aim of this work is to evaluate the impact response of four different foils when compared to a 4 mm thickness EVA sheet. Five groups of different materials were subjected to impact tests with energies of 1.72 J, 2.85 J and 4.40 J. In this context was considered the following materials: EVA foils (G1), EVA foils with an EVA foam core (G2), EVA foils with an acetate core (G3), Foils of Erkoloc-pro (G4) and Foils of Ortho IBT resin (G5). Comparisons between the materials were made by qualitative analysis of the average energy-time and load-displacement curves, as well as by comparison of the peak load, maximum displacement, contact time and absorbed energy using the Kruskal-Wallis test. It was possible to conclude that statistically significant differences were found in the energy absorbed (p=0.001). Laminated foils with a soft core (G2) are a good option to produce mouthguards, while EVA foils with an acetate core (G3) and foils of Ortho IBT resin (G5) were declared unsuitable.